The white matter of the human cerebrum: Part I The occipital lobe by Heinrich Sachs. (January 2015) - Forkel, Stephanie J.; Mahmood, Sajedha; Vergani, Francesco; Catani, Marco
Abstract: This is the first complete translation of Heinrich Sachs' outstanding white matter atlas dedicated to the occipital lobe. This work is accompanied by a prologue by Prof Carl Wernicke who for many years was Sachs' mentor in Breslau and enthusiastically supported his work.